Direct electron transport as a possible mechanism of electrogenic activity across a range of benthic cyanobacteria in a photosynthetic microbial fuel cell. Issue 4 (1st October 2020) - Güttler, Johanna; Kennedy, Sophie-Jean; Luimstra, Veerle M.; Wood, Susanna A.; Williams, David E.; Packer, Michael A.
ABSTRACT: Microbial electrogenic behaviour is well characterised in prokaryotes, including the exo-electrogenic soil bacteria ('metal breathers') and cyanobacteria, some of which can perform a light-induced donation of electrons to electrochemical devices. Two main methods of electron donation are proposed in these organisms; mobile electron shuttles (redox mediators), and direct electron transport where redox active moieties embedded in the bounding membrane of the organisms provide electrical connection. In this study a photosynthetic microbial fuel cell was used to investigate the mechanism of electron donation from six benthic cyanobacteria to an external electrode. There was no evidence of mobile electron shuttles donating electrons to the bio-electrochemical system using electrochemical analysis by linear sweep voltammetry in any of the species studied. This indicates the possibility that all the benthic species investigated may use direct electron transport as a mechanism of electron donation, which is better recognised in single-celled planktonic species.